Developing standardized competencies to strengthen immunization systems and workforce. Issue 11 (7th March 2019) - Traicoff, Denise; Pope, Alice; Bloland, Peter; Lal, Dharmesh; Bahl, Jhilmil; Stewart, Steven; Ryman, Tove; Abbruzzese, Molly; Lee, Carla; Ahrendts, Johannes; Shamalla, Lorraine; Sandhu, Hardeep
Highlights: International collaboration produced standard competencies for immunization workers. The innovative competencies design can be customized based on country needs. The three-part competency framework links to immunization program objectives. The framework describes immunization competencies for eight domains at four levels. Methodical competency modeling is a useful tool for complex immunization systems. Abstract: Despite global support for immunization as a core component of the human right to health and the maturity of immunization programs in low- and middle-income countries throughout the world, there is no comprehensive description of the standardized competencies needed for immunization programs at the national, multiple sub-national, and community levels. The lack of defined and standardized competencies means countries have few guidelines to help them address immunization workforce planning, program management, and performance monitoring. Potential consequences resulting from the lack of defined competencies include inadequate or inefficient distribution of resources to support the required functions and difficulties in adequately managing the health workforce. In 2015, an international multi-agency working group convened to define standardized competencies that national immunization programs could adapt for their own workforce planning needs. The working group used a stepwise approach to ensure that the competencies would align with immunization programs' objectives. The first step defined the attributes of a successful immunization program. The group then defined the work functions needed to achieve those attributes. Based on the work functions, the working group defined specific competencies. This process resulted in three products: (1) Attributes of an immunization program described within eight technical domains at four levels within a health system: National, Provincial, District/Local, and Community; (2) 229 distinct functions within those eight domains at each of the four levels; and (3) 242 competencies, representing eight technical domains and two foundational domains (Management and Leadership and Vaccine Preventable Diseases and Program). Currently available as a working draft and being tested with immunization projects in several countries, the final document will be published by WHO as normative guidelines. Vertical immunization programs as well as integrated systems can customize the framework to suit their needs. Standardized competencies can support immunization program improvements and help strengthen effective health systems.